Diagnostic stability in young children at risk for autism spectrum disorder: a baby siblings research consortium study - Ozonoff, Sally (J Child Psychol Psychiatry, 2015)
BACKGROUND: The diagnosis of autism spectrum disorder (ASD) made before age 3 has been found to be remarkably stable in clinic- and community-ascertained samples. The stability of an ASD diagnosis in prospectively ascertained samples of infants at risk for ASD due to familial factors has not yet been studied, however. The American Academy of Pediatrics recommends intensive surveillance and screening for this high-risk group, which may afford earlier identification. Therefore, it is critical to understand the stability of an ASD diagnosis made before age 3 in young children at familial risk. METHODS: Data were pooled across 7 sites of the Baby Siblings Research Consortium. Evaluations of 418 later-born siblings of children with ASD were conducted at 18, 24, and 36 months of age and a clinical diagnosis of ASD or Not ASD was made at each age. RESULTS: The stability of an ASD diagnosis at 18 months was 93% and at 24 months was 82%. There were relatively few children diagnosed with ASD at 18 or 24 months whose diagnosis was not confirmed at 36 months. There were, however, many children with ASD outcomes at 36 months who had not yet been diagnosed at 18 months (63%) or 24 months (41%). CONCLUSIONS: The stability of an ASD diagnosis in this familial-risk sample was high at both 18 and 24 months of age and comparable with previous data from clinic- and community-ascertained samples. However, almost half of children with ASD outcomes were not identified as being on the spectrum at 24 months and did not receive an ASD diagnosis until 36 months. Thus, longitudinal follow-up is critical for children with early signs of social-communication difficulties, even if they do not meet diagnostic criteria at initial assessment. A public health implication of these data is that screening for ASD may need to be repeated multiple times in the first years of life. These data also suggest that there is a period of early development in which ASD features unfold and emerge but have not yet reached levels supportive of a diagnosis.